(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: The purpose of this study was to determine the effectiveness of the supervision of the Head of administration of the village in the district Talawaan North Minahasa regency. Research using qualitative methods. The informants were 12 people consisting of: Head, Head of Governments of the District, 3 Village Head, 3 administrators BPD, and 3 administrators LPMD. Collecting data with interview techniques; while the data were analyzed using qualitative analysis techniques interactive model of Miles and Hubernann. Based on the results of the study it can be concluded: (1) Control Head of the administration of the village in the district of North Minahasa Regency Talawaan effective enough views of things: the supervision of the preparation and implementation of regulations and rules village head; supervision orderly implementation of village administration; Supervising the management of village finances; supervising the implementation of the tasks and performance of the village head and village; supervision of the implementation of the tasks and functions of BPD; supervision of the implementation of tasks and functions LPMD; means / measures to evaluate the administration of the village; means / measures correcting irregularities in the administration of the village administration. (2) Control Head can realize Effectiveness village governance. Based on the conclusion of the study suggested: (1) Head should be more exercise direct supervision that is down to the villages to monitor and evaluate the direct administration of the village. (2) Control Head in governance be of more preventive village. Keywords: Effectiveness, Oversight, Village Government.